Dignitaries-Abboud, Ferik Ibrahim-0011
OUT OF THE FIELD, college vice-president Irwin Addicott explains part of the defoliation demostration by a helicopter and ground machines. Following the demontration Presodent Abboud viewed the functions of a irrigation system.